2016
DOI: 10.1007/s13402-016-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 in serum-derived extracellular vesicles as a potential biomarker for hematologic malignancies - a short report

Abstract: Our data indicate that EV miR155 may serve as an attractive new, non-invasive diagnostic biomarker in human hematologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 40 publications
6
58
1
Order By: Relevance
“…This group found that the EV miR155 levels were significantly higher in CLL cases compared to controls. Conversely, they found no differences in this miR expression levels within both DLBCL and FL cases compared to controls [47]. The difference in the expression levels between our study and theirs considering DLBCL and FL may be referred to a possible difference in the genetic background of the involved subjects between their study and ours.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This group found that the EV miR155 levels were significantly higher in CLL cases compared to controls. Conversely, they found no differences in this miR expression levels within both DLBCL and FL cases compared to controls [47]. The difference in the expression levels between our study and theirs considering DLBCL and FL may be referred to a possible difference in the genetic background of the involved subjects between their study and ours.…”
Section: Discussioncontrasting
confidence: 78%
“…Additionally, EV miR155 ROC curve analyses revealed significantly different pattern in CLL when compared to controls (AUC=0.874, p=0.004). Their sensitivity and specificity were 78% and 87.5% respectively at cut-off value of 17.0 [47]. However, their ROC comparison was regarding CLL alone and only versus controls unlike ours which was for different B-cell malignancies against each other's for the purpose of sub-classification which keeps the point of novelty to our research.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…EVs contain genetic and proteomic material from originating cells, thus potentially consisting of a source of potential biomarkers [95,96,97,98]. It has been reported that EVs can be recovered from different biological fluids (e.g., serum, saliva, urine, milk) [93,99,100] suggesting a new perspective for the management of cancer; in fact, they could be used as potential biomarkers by introducing a new concept of “liquid biopsy” [93].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…This review has specially focused on Hodgkin and Non-Hodgkin Lymphomas, since other hematological diseases including leukemias and multiple mieloma microRNA-155 levels were significantly lower in multiple mieloma (MM), BL, FL and DLBCL [79].…”
Section: Other Liquid Tumorsmentioning
confidence: 99%